Retention of a resin-based sealant and a glass ionomer used as a fissure sealant: A comparative clinical study - Subramaniam P; Konde S; Mandanna D (Wolters Kluwer Medknow Publications, 2008)
Sealing occlusal pits and fissures with resin-based sealants is a proven method of preventing occlusal caries. Retention of the sealant is very essential for its efficiency. This study evaluated the retention of glass ionomer used as a fissure sealant when compared to a self-cure resin-based sealant. One hundred and seven children between the ages of 6-9 years, with all four newly erupted permanent first molars were selected. Two permanent first molars on one side of the mouth were sealed with Delton, a resin-based sealant, and the contralateral two permanent first molars were sealed with Fuji VII glass ionomer cement. Evaluation of sealant retention was performed at regular intervals over 12 months, using Simonsen′s criteria. At the end of the study period, the retention of the resin sealant was seen to be superior to that of the glass ionomer sealant.